PEDIATRIC OPTIC PATHWAY GLIOMA: DIENCEPHALIC SYNDROME - A. F. Valiakhmetova; N. A. Mazerkina; L. I. Papusha; O. I. Bydanov; E. M. Tarasova; O. A. Medvedeva; N. K. Serova; L. A. Lazareva; L. V. Shishkina; Yu. Yu. Trunin; G. A. Novichkova; S. K. Gorelyshev; et al. (Сибирский онкологический журнал, 2021)
Diencephalic cachexia (DC ) is a metabolic disorder characterized by a decrease in body weight. DC usually occurs in the presence of glioma brain tumors extended into the optic pathway. These tumors are very aggressive and have poor prognosis.Objective: to analyze the clinical course of optic pathway gliomas (OPG s) in patients with and without DC .Material and Methods. The study included 264 patients aged 0 to 18 years with an initial diagnosis of OPG s registered in the N.N. Burdenko National Medical Research Center of neurosurgery from 01/01/2003 to 12/31/2015. Patients were divided into two groups: without DC (204 people) and with DC (60 children). Results: neurofibromatosis type I (NFI) was much more common in children without DC , and pilomyxoid histology was much more prevalent in children with DC . Five-year overall survival (OS ) and event-free survival EFS were significantly lower in children with DC than in children without DC (82 ± 5 % and 96 ± 1 %, respectively versus 37 ± 7 % and 62 ± 3 %, respectively). It was found that in the DC group, the OS and EFS rates were significantly lower in girls, in children without NFI, in children without histological verification and in children with pilocytic astrocytomas. It was also found that in the DC group, OS rates were significantly lower in children under 1 year, and EFS rates were significantly lower in children aged more than 12 months. The number of patients without events were significantly higher in the group without DC (p=0.001). The number of deaths in the postoperative period was significantly higher in children with DC (p<0.001). Diabetes insipidus and hyponatremia were significantly more common in patients with diencephalic cachexia, and vision improvement after treatment was significantly more likely to occur in patients without DC .Conclusion. OPG s in patients with DC have a more aggressive clinical course, which requires more careful treatment and observation.